High survival following bleaching underscores the resilience of a frequently disturbed region of the Great Barrier Reef. Issue 2 (13th February 2023) - Page, Cathie A.; Giuliano, Christine; Bay, Line K.; Randall, Carly J.
Abstract: Natural bleaching events provide an opportunity to examine how local‐scale environmental variation influences bleaching severity and recovery. During the 2020 marine heat wave, we documented widespread and severe coral bleaching affecting 75%–98% of coral cover throughout the Keppel Islands in the southern inshore Great Barrier Reef. Acropora, Pocillopora, and Porites were the most severely affected genera, while Montipora was comparatively less susceptible. Site‐specific heat‐exposure metrics were not correlated with Acropora bleaching severity, but recovery was faster at sites that experienced lower heat exposure. Despite severe bleaching and exposure to accumulated heat that often results in coral mortality (degree heating weeks 4–8), cover remained stable. Approximately 94% of fate‐tracked Acropora millepora colonies survived, perhaps due to reduced irradiance stress from high turbidity, heterotrophic feeding, and large tidal flows that can increase mass transfer. Severe bleaching followed by rapid recovery and the continuing dominance of Acropora populations in the Keppel Islands is indicative of high resilience. These coral communities have survived a 0.8°C increase in average temperatures over the last 150 years. However, recovery following the 2020 bleaching was driven by the easing of thermal stress, which may challenge their recovery potential under further warming.